Self-Efficacy And Social Support In Relation To Fear Of Failure Among Job Seekers - Pandi Nurhadi; Andik Matulessy; Amanda Pasca Rini (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
University graduate job seekers in Indonesia face intense labor market competition, which may give rise to fear of failure. This study aimed to examine the relationship between self-efficacy and social support with fear of failure among job seekers. A quantitative correlational design was employed, involving 314 job seekers under the age of 29 who held a university degree, selected through purposive sampling. Data were collected using three Likert-type scales: a fear of failure scale adapted from the Performance Failure Appraisal Inventory (Conroy et al., 2002), a self-efficacy scale based on the dimensions of level, strength, and generality (Bandura, 1997), and a social support scale based on the dimensions proposed by Cutrona and Russell (1987). Data were analyzed using multiple regression with SPSS version 27. The results showed that self-efficacy and social support were simultaneously and significantly negatively related to fear of failure (R = .572, R² = .327, p < .001), accounting for 32.7% of the variance. Partially, self-efficacy (t = -6.421, p < .001) contributed more strongly than social support (t = -3.473, p < .001) in predicting fear of failure. These findings highlight the importance of strengthening self-efficacy and social support networks as psychological intervention strategies for job seekers navigating a competitive labor market.